2018
DOI: 10.1167/iovs.18-24160
|View full text |Cite
|
Sign up to set email alerts
|

Peripapillary Retinoschisis in Glaucoma: Association With Progression and OCT Signs of Müller Cell Involvement

Abstract: PurposeTo examine demographic and clinical factors associated with glaucomatous peripapillary retinoschisis (PPRS) and assess its association with glaucoma progression.MethodsUsing a case control study design and longitudinal data from a cohort of 166 subjects with a diagnosis of glaucoma or glaucoma suspect, we compared functional, structural, clinical, and demographic characteristics between PPRS cases and controls.ResultsThe frequency of PPRS was 6.0% (12 eyes from 10/166 subjects) with two eyes having PPRS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
52
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 34 publications
(54 citation statements)
references
References 49 publications
(96 reference statements)
2
52
0
Order By: Relevance
“…Other investigators have indicated the contrary, that the inner retinal schisis precedes the formation of the central serous detachment. However, cases where only an inner retinal schisis is present without a central serous detachment has also been documented . The variability of these presentations have been suggested to be contingent upon the presence of vitreo‐retinal traction, the volume of intravitreal fluid collection proximal to the optic pit and the outer retinal lamellar macular defects .…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Other investigators have indicated the contrary, that the inner retinal schisis precedes the formation of the central serous detachment. However, cases where only an inner retinal schisis is present without a central serous detachment has also been documented . The variability of these presentations have been suggested to be contingent upon the presence of vitreo‐retinal traction, the volume of intravitreal fluid collection proximal to the optic pit and the outer retinal lamellar macular defects .…”
Section: Discussionmentioning
confidence: 99%
“…Another possible explanation to account for the long‐term stability may be related to the integrity of the Muller cells. For example, it has been documented that induced ablation of the Muller cells produce a spontaneous schisis at the inner retina . It has also been suggested that Muller cell anomalies may contribute to the pathogenies of X‐linked retinoschisis and analogous inter‐cellular adhesion defects in stellate nonhereditary idiopathic retinoschisis .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations